Enhanced prognostic value of a composite nutritional-inflammatory index (P-CONUT) for predicting mortality risk in patients initiating peritoneal dialysis - Xing Li; Xueli Zhou; Kuo Li; Li Pu; Xueqin He; Xia Liu; Hui Zhong; Dengyan Ma (PLoS ONE, 2025)
Background and Objectives Nutritional and inflammatory indicators are key to predicting outcomes in peritoneal dialysis (PD) patients. This study evaluates the prognostic value of the Prognostic Nutritional Index (PNI), Controlling Nutritional Status (CONUT) score, and a novel composite score, P-CONUT, which integrates both nutritional and inflammatory status, to improve risk prediction and management in PD patients. Methods This retrospective study included 810 PD patients. The primary outcome was all-cause mortality. Kaplan-Meier survival curves compared outcomes across groups, and log-rank tests assessed differences. Univariate and multivariate cox regression analyses identified independent mortality predictors. The prognostic performance of CONUT, PNI, and P-CONUT was evaluated using the area under the curve (AUC) and integrated AUC comparisons. Net reclassification improvement (NRI) and integrated discrimination improvement (IDI) were used to assess the incremental value of P-CONUT over CONUT and PNI. Decision curve analysis (DCA) assessed the clinical utility of the models. A nomogram incorporating significant predictors was developed to aid in prognosis prediction. Results Cox regression identified P-CONUT as an independent predictor of all-cause mortality (G2 vs. G1: HR = 0.354, 95% CI: 0.238–0.528, p < 0.001; G3 vs. G1: HR = 0.385, 95% CI: 0.270–0.549, p < 0.001). P-CONUT demonstrated superior prognostic performance (AUC = 0.790, 95% CI: 0.751–0.829), with improvements over CONUT (AUC = 0.611, 95% CI: 0.561–0.661) and PNI (AUC = 0.636, 95% CI: 0.587–0.686). The NRI for P-CONUT over CONUT and PNI was 0.331 (95% CI: 0.156–0.408) and 0.357 (95% CI: 0.221–0.428), respectively. The IDI for P-CONUT compared to CONUT and PNI was 0.111 (95% CI: 0.011–0.145) and 0.112 (95% CI: 0.018–0.149), respectively. DCA demonstrated that P-CONUT provided a greater net benefit than both CONUT and PNI across a range of risk thresholds. Conclusion P-CONUT is a strong independent predictor of mortality in PD patients, outperforming both CONUT and PNI in prognostic accuracy. The composite P-CONUT score, integrating both nutritional and inflammatory status, provides superior predictive value, aiding in more precise risk stratification. This score, coupled with other significant prognostic factors, offers a reliable tool for improving the long-term management and clinical decision-making for PD patients.